MnFe0.5Ru0.5O3: an above-room-temperature antiferromagnetic semiconductor. Issue 3 (5th December 2018) - Tan, Xiaoyan; McCabe, Emma E.; Orlandi, Fabio; Manuel, Pascal; Batuk, Maria; Hadermann, Joke; Deng, Zheng; Jin, Changqing; Nowik, Israel; Herber, Rolfe; Segre, Carlo U.; Liu, Sizhan; et al.
Abstract : MnFe0.5 Ru0.5 O3 is discovered at 6 GPa and 1873 K. Abstract : A transition-metal-only MnFe0.5 Ru0.5 O3 polycrystalline oxide was prepared by a reaction of starting materials MnO, MnO2, Fe2 O3, RuO2 at 6 GPa and 1873 K for 30 minutes. A combination of X-ray and neutron powder diffraction refinements indicated that MnFe0.5 Ru0.5 O3 adopts the corundum (α-Fe2 O3 ) structure type with space group R 3̄ c, in which all metal ions are disordered. The centrosymmetric nature of the MnFe0.5 Ru0.5 O3 structure is corroborated by transmission electron microscopy, lack of optical second harmonic generation, X-ray absorption near edge spectroscopy, and Mössbauer spectroscopy. X-ray absorption near edge spectroscopy of MnFe0.5 Ru0.5 O3 showed the oxidation states of Mn, Fe, and Ru to be 2+/3+, 3+, and ∼4+, respectively. Resistivity measurements revealed that MnFe0.5 Ru0.5 O3 is a semiconductor. Magnetic measurements and magnetic structure refinements indicated that MnFe0.5 Ru0.5 O3 orders antiferromagnetically around 400 K, with magnetic moments slightly canted away from the c axis. 57 Fe Mössbauer confirmed the magnetic ordering and Fe 3+ ( S = 5/2) magnetic hyperfine splitting. First principles calculations are provided to understand the electronic structure more thoroughly. A comparison of synthesis and properties of MnFe0.5 Ru0.5 O3 and related corundum Mn2 BB′O6 derivatives is discussed.